Aim of Political Philosophy - Jokubaitis, Alvydas (Problemos, 2007)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian]Over the last few decades, political philosophers have been formulating the identity of their discipline not merely in terms of their inner objective. An aggressive attack of political scientists contributed significantly towards the perception of the identity of political philosophy. The definition of the purpose of political philosophy became dependent on the existence of a strong external opponent. This was hardly the case with the political philosophers representing the former generations. They contributed towards development of political philosophy without thinking about guard against representatives of other sciences. During the last few decades, political philosophers have come up with the definition of the purpose of their discipline. But they do not adhere to it in their real philosophical investigations. This non-adherence is caused not by the lack of professional ethics, will power or by dissimulation. Political philosophy as a discipline is too broad and controversial to be enclosed in the framework of a single definition of purpose. The definition of the purpose formulated during several decades of debates with political scientists, is oriented towards the external rather than internal use.
Keywords: political philosophy, political science, normative theory, positivism